Hysterosalpingo‐Contrast Sonography With a Saline‐Air Device Is Equivalent to Hysterosalpingography Only in the Presence of Tubal Patency. (28th April 2016) - Robertshaw, Isela M.; Sroga, Julie M.; Batcheller, April E.; Martinez, Alan M.; Winter, Thomas C.; Sinning, Kristin; Maxwell, Rose; Lindheim, Steven R.
Abstract : Objectives: To compare hysterosalpingo‐contrast sonography with a saline‐air device to hysterosalpingography for evaluating tubal patency. Methods: Eighty women undergoing infertility evaluations were recruited for this prospective cohort study. All patients underwent both office‐based hysterosalpingo‐contrast sonography with a saline‐air device and hysterosalpingography as the reference standard, and the fallopian tubes were individually assessed for tubal patency in each procedure. The Cohen κ coefficient was used to assess agreement between each procedure, and the Student t test and χ 2 test were used to compare differences in time, pain, and procedural preference. Results: In total, 75 patients with 148 fallopian tubes were evaluated. Tubal patency on hysterosalpingo‐contrast sonography with the saline‐air device was noted in 85.8% (n = 127) of tubes compared to 92.5% (n = 137) on hysterosalpingography, with a positive predictive value of 95.2%. Tubal occlusion was noted in 21 tubes (14.2%) on hysterosalpingo‐contrast sonography compared to 11 (7.4%) on hysterosalpingography, with a negative predictive value of 23.8% (24 of 28). Overall, hysterosalpingo‐contrast sonography agreed with hysterosalpingography in 126 of 148 fallopian tubes (85.1%; κ = 0.47; P < .001). The procedural time and pain scores were significantly greater for hysterosalpingo‐contrast sonography compared to hysterosalpingography. Conclusions: There was a significant degree of agreement between hysterosalpingo‐contrast sonography with a saline‐air device and hysterosalpingography when the fallopian tube was patent but not when it was occluded. In the absence of patency, further evaluations with hysterosalpingography may be indicated to avoid false‐positive results. Although the procedure time and degree of pain appear to be greater, avoidance of radiation exposure by using hysterosalpingo‐contrast sonography with a saline‐air device may outweigh the drawbacks.